Yield and quality of five BMR sorghum varieties in the dry tropics of Costa Rica - Camacho-Montero, José Roberto (2026)
Introduction. Sorghum (Sorghum bicolor L. Moench) is a C4 grass recognized for its high productivity and tolerance to heat and drought stress, widely used in animal feeding. The incorporation of the brown midrib (BMR) gene enhances its forage value by reducing fiber content and increasing digestibility. Objective. To evaluate the productive performance and bromatological quality of five BMR sorghum varieties, in order to identify promising lines for use as a forage resource in livestock systems of the dry tropics. Materials and methods. The study was conducted at the Centro de Innovación Agropecuaria Enrique Jiménez Núñez (Cañas, Guanacaste, Costa Rica) during the 2020 rainy season and the 2021 dry season (under irrigation). A randomized complete block design with four replications was used. Treatments included five BMR lines (0916, 0919, 0925, 0929, and 0936), derived from crosses between BMR materials from Texas (USA) and Central American germplasm. Forage black sorghum (Sorghum almum) was used as the control. Agronomic variables and nutritional quality of fresh and ensiled forage were evaluated. Results. Although the BMR varieties showed lower biomass production and shorter crop cycles than the control, they exhibited superior nutritional quality in both seasons. Conclusions. BMR sorghum varieties showed lower biomass yield than forage black sorghum but exhibited nutritional advantages, supporting their potential as a strategic forage alternative in cattle production systems of the Costa Rican dry tropics.